Risks of Using Artificial Intelligence in Law Enforcement, Criminal Proceedings, Border Control and Migration Management - Kolarič, Katja (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
The EU is the first in the world to adopt the Artificial Intelligence Act, a single legal framework for its development. This chapter discusses the use of artificial intelligence in crime prevention, border control and migration. Artificial intelligence helps detect crime, improve law enforcement methods and investigate financial and cybercrime. However, at the same time, it can threaten fundamental rights under the Charter of Fundamental Rights of the European Union. Mass surveillance is disproportionate, and algorithmic bias can lead to discrimination. The quality of data affects the results, increasing inherent bias. It is crucial to balance the protection of rights with the effective implementation of police tasks. It is essential to follow the Ethical Guidelines when using artificial intelligence for criminal investigations, as decisions have serious consequences for the life and freedom of individuals.